Control interno y contrataciones públicas en el Gobierno Regional de Loreto durante el período 2021 – 2023 - Garcia del Aguila, Luis Martin (2025)
This analysis examines the connection between internal control and public contracting in the regional government of Loreto in the period 2021 - 2023. Through a quantitative approach and a non-experimental correlational design, data collected from a group of 80 employees were evaluated, with the main objective of establishing the relationship between internal control and public contracting in the regional government of Loreto during the period 2021-2023. The findings show a direct and significant correlation between internal control and public procurement, with a Spearman coefficient of 0.846, and (p=0.000). In relation to the control environment and public contracting, it showed a still strong relationship (Rho=0.761, p=0.000), which suggests that internal control is appropriate and timely. On the other hand, there is a direct and relevant correlation between risk assessment and public procurement (Rho=0.785, p=0.000), which reflects that there is a deep understanding in public procurement carried out by employees. Regarding the relationship between control activities and public contracting, a direct and relevant correlation was observed, which indicates that when carrying out the separation of functions, tasks are frequently delegated (Rho=0.843, p=0.000). Finally, a direct and relevant correlation was found between supervision and public contracting (Rho=0.834, p=0.000). This study provides a basis for future research and highlights the importance of improving the issue of internal control and public procurement in accordance with current regulations.